(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2025)
In radiopharmaceutical production centers and nuclear medicine services, short half-life radionuclides are essential. They have been used as radiotracers since their use increased significantly and aroused the interest of national metrology laboratories, which are responsible for providing traceability to radioactive standards. Therefore, knowledgement of the activity of administered radiopharmaceuticals must be obtained accurately. However, their short half-lives prevent the provision of traceability. To overcome these obstacles, an itinerant system based on a NaI(Tl)-type scintillator detector is being developed at the National Laboratory for Ionizing Radiation Metrology (LNMRI). This work aims to show the schematic arrangement of the system developed to calibrate activimeters, as well as the tests and experimental comparisons carried out in this study using performance indicator parameters to characterize and validate the itinerant NaI(Tl) detection system in the calibration of activimeters.